The effect of work piece velocity and depth of cut on the performance of grinding process using alumina-En9 - DNK Putra Negara; IGN Priambadi; I Ketut Suarsana (Department of Mechanical Engineering, University of Udayana, 2006)
Grinding is a very complex machining process due to many parameters to be considered. In this research, the effect of workpiece velocity and depth of cut toward performent of grinding such as actual depth of cut, force, power and specific energy to be investigated. Grinding process to be applyed is straight surface grinding with alumina and En9 as grinding wheel and workpiece respectivelly. Two independent variables to be condisioned, there are workpiece velocities ( 0,1, 0,2, and 0,3 m/s) and setting depth of cut (10, 20, 30, 40 and 50?m. The data obtained is evaluated by plooting into grapht. The results of experiment show that the higher depth of cut, the higher actual depth of cut obtained, however, the higher worcpice velocity, the lower depth of cut obtained; depth of cut and workpiece velocity are proportional to force, power and volume rate of metal removal; and specific energy is proportional to depth of cut but it is opposite to vorkpiece velocity.